O lugar do espectador na obra de Helena Almeida : a experiência de ser pintura - Silva, Viviane Soares (2019)
This article’s goal is to analyze how the curatorial project of the exhibition — “Helena Almeida: My work is my body, my body is my work” — confronts key ideas attributed to the artist’s work. Taking other readings into consideration is intended to present the terms of a (re) reading of the artist’s work within the exhibition’s framework. In conceptual terms this (re) reading is based on the assumption that the artist’s work since the 60s is a pure assertion of painting, even when the artist’s practice is extended to other media